2009
DOI: 10.1002/asl.206
|View full text |Cite
|
Sign up to set email alerts
|

Black carbon aerosol mass concentration variation in urban and rural environments of India—a case study

Abstract: The present study provides an account of the black carbon (BC) aerosol mass concentration variation in contrasting environments of India corresponding to the urban and rural areas of Hyderabad and Anantapur during August 2006. The study period corresponds to the monsoon season over the Indian region. The diurnal variation of BC showed two peaks, during morning and late evening, which are mostly, related to the diurnal changes in the local boundary layer and traffic density patterns. BC mass concentrations over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Similar annual variations of the anthropogenic aerosols have been observed within urban environments in India (Badarinath et al, 2009;Ramachandran and Kedia, 2010;Pathak et al, 2010). In addition, the boundary layer mixing height is lower in winter and traps the pollutants near the ground as a result of temperature inversions.…”
Section: Seasonal and Monthly Variability In Pm Concentrationssupporting
confidence: 65%
“…Similar annual variations of the anthropogenic aerosols have been observed within urban environments in India (Badarinath et al, 2009;Ramachandran and Kedia, 2010;Pathak et al, 2010). In addition, the boundary layer mixing height is lower in winter and traps the pollutants near the ground as a result of temperature inversions.…”
Section: Seasonal and Monthly Variability In Pm Concentrationssupporting
confidence: 65%
“…Various studies from different locations in India have reported surface BC levels Badarinath et al, 2007Badarinath et al, , 2009Latha and Badarinath, 2003;Pant et al, 2006;Tiwari et al, 2009;Ram et al, 2010;Ramachandran and Rajesh, 2007;Safai et al, 2007Safai et al, , 2008Sreekanth et al, 2007;Tripathi et al, 2005;Dumka et al, 2010;Das et al, 2009;Chowdhury et al, 2007;Kumar et al, 2011a;Pathak et al, 2010;Niranjan et al, 2006). However, studies on long term trends in BC aerosols over any location are very scarce.…”
Section: Introductionmentioning
confidence: 93%
“…Ramachandran and Rajesh, 2007;Pathak et al, 2010;Satheesh et al, 2010) its large fractions over west, north and east BoB highlight the strong anthropogenic influence and the outflow of pollutants over the marine environment during winter. It may also be noted that BC concentrations are larger during winter season throughout the Indian sub-continent (Badarinath et al, 2009b). An interesting feature that is revealed from Table 3 is the nearly absence of mineral-transported aerosols corresponding to dust particles; however, they exhibit larger fraction over west BoB justified from the chemical analysis of the IGP outflow .…”
Section: Opac Simulationsmentioning
confidence: 99%